Analysis of SWOT: Human Resource Management in Supporting the Potential and Attraction of Gampong Cinta Raja Tourism in Langsa City - Lindanisrina, Lindanisrina; Chandra, Riny; Maulidan, Rahmat; Maula, Ziaul (Jurnal EMT KITA, 2026)
This study aims to analyze human resource (HR) management in supporting the tourism potential and attractions in Gampong Cinta Raja Tourism Village, Langsa City. The research objects include the village's main potentials in the form of migratory bird ecotourism, mangrove areas, and thorny pandan crafts, which are the identity of the community's creative economy. The research method uses a descriptive qualitative approach with data collection techniques such as interviews, observation, and documentation. Data analysis was conducted using the IFAS, EFAS, and SWOT matrices. The results show that the village has strengths in the form of community support, the active role of Pokdarwis, and unique natural potential that can attract tourists. However, weaknesses were found such as minimal HR managerial skills, less than optimal digital promotion, and limited tourism facilities. Development opportunities are obtained from government support and the increasing trend of nature tourism, while threats include competition from other tourism villages and environmental factors that affect the sustainability of migratory bird attractions. This study recommends increasing human resource capacity, strengthening digital promotion, improving tourism support facilities, and developing collaborations with the government, academics, and related communities to support the sustainability and competitiveness of Gampong Cinta Raja Tourism Village.